Current Status and Future Perspectives on the Etiology of Esophageal Adenocarcinoma - Thrift, Aaron P.; Pandeya, Nirmala; Whiteman, David C. (Frontiers in Oncology, 2012)
Esophageal adenocarcinoma is the most common type of esophageal cancer in most Western countries and is an important contributor to overall cancer mortality. Most cases of esophageal adenocarcinoma are believed to arise from Barrett’s esophagus. Esophageal adenocarcinoma occurs more frequently in white men over 50 years old, as well as in people with frequent symptoms of gastroesophageal reflux, in smokers and in people who are obese. Higher consumption of fruit and vegetables, use of non-steroidal anti-inflammatory drugs, and infection with Helicobacter pylori have all been shown to reduce the risk of esophageal adenocarcinoma. Here, we review the epidemiological evidence for the major risk factors of esophageal adenocarcinoma and also discuss perspectives for future research.